Masa Depan Pendidikan Islam Di Era Digital - Kohar, Kohar (Jurnal Ilmiah Al-Hadi, 2023)
This paper aims to discuss how Islamic education programmes are structured and adapted to the needs of the modern era and achieve the expected results through such education. The modern era is characterised by rapid technological advancements, where generations of learners tend to be more skilled in using modern devices since their childhood, in contrast to previous generations who may be less familiar with technology. Because of this difference, it is important to adjust the Islamic education curriculum to be relevant to the lifestyles and preferences of learners who come from this modern generation. This paper is a synthesis of various thoughts that have been reviewed through a literature research approach, which aims to find pre-existing ideas and findings. The purpose of this synthesis is to formulate new ideas in response to the challenges and opportunities that arise in this technological era. This is important because the world is constantly changing and evolving, so Islamic education must also adapt to remain relevant and effective. What needs to be emphasised in the development of Islamic education in this modern era is the adaptation of learning materials into digital formats as well as nurturing generations of Muslims to achieve success. Adaptation of learning materials into digital formats is important to facilitate learning that is more interactive, accessible, and in line with the preferences of modern generations of learners who are more likely to use technology in their daily lives. Meanwhile, fostering a generation of Muslims to achieve success both in this world and the hereafter emphasises the importance of personality development, skills, and Islamic values that can guide them towards a fruitful and harmonious life.